2009
DOI: 10.1007/s00384-009-0678-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and instrumental parameters in patients with constipation and incontinence: their potential implications in the functional aspects of these disorders

Abstract: This study has demonstrated strong correlations between physiatric disorders and the symptoms of constipation and incontinence. Further studies designed to demonstrate a causal relationship between these parameters and the success of a specific treatment of the physiatric disorders on the proctology symptoms are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Overall, 63 studies published between 1984 and 2017 contributed to the systematic review, providing data on the diagnostic yield of 7519 barium defecographies (range, 40‐896 per study) and 668 MRIDs (range, 40‐188 per study) in patients with CC, and 225 barium defecographies (range, 8‐47 per study) and 50 MRIDs (n = 1 study) in HV (Table ). Overall, only 9 (14%) studies were controlled using either healthy (n = 2) or nonhealthy (n = 3; eg, patients presenting for investigation of other complaints) volunteers, or a combination of both subjects (n = 4) …”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 63 studies published between 1984 and 2017 contributed to the systematic review, providing data on the diagnostic yield of 7519 barium defecographies (range, 40‐896 per study) and 668 MRIDs (range, 40‐188 per study) in patients with CC, and 225 barium defecographies (range, 8‐47 per study) and 50 MRIDs (n = 1 study) in HV (Table ). Overall, only 9 (14%) studies were controlled using either healthy (n = 2) or nonhealthy (n = 3; eg, patients presenting for investigation of other complaints) volunteers, or a combination of both subjects (n = 4) …”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
“…Among the 59 studies in patients with CC, diagnostic criteria and prevalence of functional abnormalities were provided in 42 (71%), based on either (a) (n = 22); (b) (n = 2); (c) (n = 2); (a + b) (n = 4); (a + c) (n = 7); (b + c) (n = 1); or (a + b+c) (n = 4) . Quantitative meta‐analysis of these studies, including four comparative (barium defecography vs MRID) studies, showed a pooled prevalence of 24.1% (95% CI, 20.2‐28.4) on barium defecography and 25.9 (14.1‐39.6) on MRID (Figure S6).…”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
“…Four studies evaluated concurrent positivity of US and ARM. These were conducted by three groups, all in surgical departments, one in Brazil and two in Europe and included a total of 279 patients. Concurrent positivity for US among those with positive ARM ranged from 68.4% to 88.6% and the median prevalence of combined positivity (positive on both tests) was 37.6% (range 9.3–46.4).…”
Section: Resultsmentioning
confidence: 99%
“…However, we did consider anal sphincter operation as a criteria to be assigned to the comorbidity subgroup. Furthermore, as demonstrated by Brusciano and others, it would be interesting to add clinical-functional measurements to demonstrate the underlying factors of FI in a follow-up study [22, 23]. …”
Section: Discussionmentioning
confidence: 99%